ANALISIS FAKTOR KEBISINGAN BERDASARKAN ASPEK LINGKUNGAN DI PERSIMPANGAN JALAN KOTA PAREPARE - Suci Ramadani; Rahmi Amir; Fitriani Umar (LPPM STIKes Prima Indonesia, 2020)
Noise then cross street highway is a noise that disturbs the activities basic human break,communication, study, and work. Pollution sound caused, volume high that makes the areaaround it becomes noisy. Pollution sound with level noise in on from 85 dB result in effectbad for health human, destination research for knowing level noise in Crossroad StreetAgussalim to Street Karaeng Buranne and Street Bau Massepe to Street Karaeng Buranne.Type research that used that is descriptive, a tool that used that is sound level meters, standssound level meters, sheet observation, the sample as much 60 people including the user streetand public that there is around crossroads. Taking data measurement noise during theinterval time 10 minutes that in do it in the morning, noon and afternoon. The resultsmeasurement in Crossroad Street Agussalim to Street Karaeng Buranne and Street BauMassepe to Street Karaeng Buranne on when sound voice announcer more high-level noiseon morning day with amount volume vehicle 465 average 76,7 dB, while on when afternoonday level noise decreased with amount volume vehicle 402 average 72,5 dB, thus too on whenno sound voice announcer more high-level noise on morning day with average 74,4 dB, whileon afternoon day level noise decreased with average 71,8 dB. Perception public about toolgiver gesture light traffic stated 63,3% well and 36,7% stated less well. Picture aboutregulation placement APILL in crossroad street still many public around to do violation andpermanent indifferent to appeal or voice announcer that there is a traffic light. The necessitysocialization sign traffic in the street so that no occur violation that can cause accident traffic.